Sugar heritage and tourism in transition - Jolliffe, Lee (Tourism and cultural change, 2013)
This book examines the sugar and tourism relationship in the context of globalization by identifying destination transitions from sugar to tourism. It profiles the role of sugar in colonization, enslavement, decolonization and postcolonial tourism, offering examples of sugar heritage in tourism from all over the world.